(untitled) (Journal of Oriental Studies, 2016)
In the article we have analyzed the interconnection between the level of education and employment rates of Indian women. Special interest lies in the phenomena of unequal distribution of education among men and women and simultaneously, unequal growth of literacy rates among them. The article is an overview of the presented issues and tendencies. Keywords: